طرق إبرام عقود تفويض المرفق العام في ظل المرسوم التنفيذي 18-199 - كرميش إيمان (جامعة محمد بوضياف المسيلة, 2019)
إن عقد التسيير المفوض من العقود الإدارية التي تجمع بين طرفين المفوض والمفوض له، يتمثل محتواها في تحصيل أموال مقابل الخدمات المقدمة، خلال مدة محددة وفقا لإجراءات معينة ووفقا لأشكال مختلفة، وبالتالي فهو يشكل نظاما قانونيا قائما بذاته يتطلب دراسة من جوانب مختلفة. يتناول موضوع البحث "طـــرق إبرام عقــــود تفويضات المرفق العــــــام في ظل المــــرسوم التنفيذي رقم 18-199 بدراسة صيغ إبرام عقود التفويض، لقد عمد المشرع الجزائري في تفويضات المرفق العام إلى وضع صيغتين تتمثل الصيغة الأولى في الطلب على المنافسة كقاعدة عامة، أما الثانية فتمثلت في التراضي كاستثناء إلى جانب ذلك، ألزم المشرع السلطة المفوضة عند اختيار المفوض له بضرورة إتباع الإجراءات القانونية لكل مرحلة من مراحل إبرام هذا العقد مقيدا بذلك سلطتها في الإختيار كل ذلك في إطار احترام المبادئ المنصوص عليها في المادة 5 من المرسوم الرئاسي رقم 15-247 واحترام المرفق عند تنفيذ إتفاقية تفويضه لمبادئ الاستمرارية والمساواة والقابلية للتكيف مع ضمان معايير الجودة والنجاعة في الخدمة العمومية. إن ضمان المنح العادل لعقد التفويض لا يتأت إلا بوضع المنافسة موضع التطبيق الفعلي وذلك بتحديد الأساليب ومجموعة من الإجراءات التي تنظم عملية إبرام عقود تفويض المرفق العام لتحقيق الأهداف المتوخاة من ذلك، وتحقيق الوصول إلى أهداف جلية في مساهمة هذا البحث وإثراء الموضوع محل الدراسة. الكلمات المفتاحية: إجراءات الإبرام، العقود الإدارية، تفويض المرفق العام،المنافسة والشفافية، المساواة،السلطة المفوضة، المفوض له. Abstract The authorized management contract of the administrative contracts between the authorized and delegated parties is consisted provided services within a specified period in accordance with certain procedures and in different forms,and thus it constitutes a stand-alone legal system that requires examination of various aspacts. The topic of the study is "the Concluding Contract Methods for the general assembly's mandates under executive decree no 18_199 on the modalities of the conclusion of authorizations,The Algerien legislator has delegated the General Assembly's mandates to the formulation of two formulas:the first is to demand competition as a general rule,the second is to gree as an exception. In addition,the legislator requires from the delegated authority in the selection of the commissioner the need to follow the legal procedures for each stage of the conclussion of this contract thereby restricting its its power of choice,all this the framework of respecting the principles set sorth in article 5 of presendtial decree 15_247,continuity,equality and adaptability to ensure quality and efficiency standards in the public service. Ensuring equitable grant of a mandate is only possible by putting competition into practice by defining the modalities and set of procedures governing the conclusion of the general Assembly's mandate contracts to achieve the objectives and achieving clear objectives in the contribution of this research and enriching the topic under consideration. key words: conducting contract, administrative contracts, public service delegation, competition and trensparency, equality, delegated authority, delegate.
Keywords: إجراءات الإبرام، العقود الإدارية، تفويض المرفق العام،المنافسة والشفافية، المساواة،السلطة المفوضة، المفوض له.